Reinforced Concrete with Graphene Oxide: Techno-Economic Feasibility for Reduced Cement Usage and CO2 Emissions - D. Domínguez-Santos; P. Muñoz; J. O. Morales-Ferreiro; C. Acuña; D. E. Diaz-Droguett; Elvira Villaro (International Journal of Concrete Structures and Materials)
Abstract Concrete, a key material in modern infrastructure, significantly contributes to global CO2 emissions, urging innovative approaches for its environmental impact mitigation. This study evaluates the techno-economic feasibility of incorporating graphene oxide (GO) into concrete formulations to enhance mechanical properties and reduce cement usage, thereby mitigating CO2 emissions. The methodology involved synthesising GO using a modified Hummers’ method, ensuring uniform dispersion in concrete matrices. Concrete samples with varying GO contents underwent mechanical strength testing, as well as microstructural analysis including SEM, XPS, and Raman spectroscopy. Results led to simulations of the mechanical response of low- and medium-rise buildings subjected to seismic forces. Besides, economic assessments were performed by considering the overall cost of materials (GO and concrete) and the savings from CO2 emissions, based on different scenarios for both GO and CO2 prices. The optimal formulation uses 0.1% GO by weight of cement, improving compressive strength by up to 17.92% and flexural strength by up to 74.78%. Structural models indicate that GO can reduce the weight of structural elements by 8–24%, leading to lower seismic forces and easier compliance with seismic-resistant standards. Economic analysis reveals that low-rise buildings can benefit from GO-enhanced concrete if the GO price is between €50 and €80 per kg, depending on CO2 credit prices ranging from €60 to €200 per tonne. For taller buildings, the economic feasibility is more restrictive; GO prices must be between €50 and €70 per kg with CO2 credit prices starting at €100 per tonne to justify the use of 0.1% GO. Graphical Abstract